Effects of acidification on mercury methylation, demethylation, and volatilization in sediments from an acid-susceptible lake. - Steffan, R J (1988)
The effect of experimental acidification on mercury methylation, demethylation, and volatilization was examined in surficial sediment samples from a weakly buffered northern Wisconsin lake. All mercury transformations were measured with radioisotopic tracers. Acidification of sediment pH with H2SO4, HCl, or HNO3 significantly decreased 203Hg(II) methylation. Acidification of pH 6.1 (ambient) sediments to pH 4.5 with either H2SO4 or HCl inhibited methylation by over 65%. The decreased methylation was due to the increased hydrogen ion concentration because methylation was not affected by concentrations of Na2SO4 or NaCl equimolar to the amount of acid added. Inhibition of methylation was observed even after prolonged acidification of sediments to pH 5.0 for up to 74 days. Acidification of sediments to pH 5.5, 4.5, and 3.5 with HNO3 resulted in a near complete inhibition of methylation at each pH. Similarly, the addition of equimolar amounts of NaNO3 resulted in a near complete inhibition of methylation, indicating that the inhibition was due to the nitrate ion rather than to the acidity. Demethylation of methyl mercury was not affected by pHs between 8.0 and 4.4, but sharply decreased below pH 4.4. Volatilization of 203Hg(II) from surface sediments was less than 2% of methylation activity and was not significantly different from that in killed sediments. This study indicated that acidification of sediments inhibits mercury methylation and that the observed increase in the mercury burdens in fish from low pH lakes is not due to increased production of methylmercury in sediments.